Pengajian Sabilussalam dan Perannya Dalam Meningkatkan Spiritualitas dan Moderasi Beragama Umat - Solechan Solechan (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This research aims to analyze the role of sabilussalam recitation in improving the spiritual attitudes and religious moderation of residents of Sugiharjo village, Tuban District. This research uses a qualitative approach with a case study type of research. The first research result was that the Sabilussalam recitation was carried out in rotation in the congregation's homes every Friday night. The material presented includes reading yasin and tahlil letters, reading sholawat dibaiyah, and maidhoh hasanah. The method used in recitation is the lecture and question and answer method. Second, the spiritual improvement of Sugiharjo village residents includes increasing faith and piety, religious awareness, and concern. Third, the moderate attitude of Sugiharjo village residents is divided into moderate attitudes in matters of faith and moderate attitudes in matters of worship. A moderate attitude in faith includes tolerating differences in schools of thought, avoiding takfiri attitudes and avoiding fanaticism. A moderate attitude in worship matters is tolerance towards religious practices, active participation in social and religious activities, and respect for differences in understanding of beliefs.